Cross Layer PHY-MAC Protocol for Wireless Static and Mobile Ad Hoc Networks. (4th August 2008) - Romaszko Romaszko, Sylwia Sylwia; Blondia Blondia, Chris Chris
Abstract : Multihop mobile wireless networks have drawn a lot of attention in recent years thanks to their wide applicability in civil and military environments. Since the existing IEEE 802.11 distributed coordination function (DCF) standard does not provide satisfactory access to the wireless medium in multihop mobile networks, we have designed a cross-layer protocol, (CroSs-layer noise aware power driven MAC (SNAPdMac)), which consists of two parts. The protocol first concentrates on the flexible adjustment of the upper and lower bounds of the contention window (CW) to lower the number of collisions. In addition, it uses a power control scheme, triggered by the medium access control (MAC) layer, to limit the waste of energy and also to decrease the number of collisions. Thanks to a noticeable energy conservation and decrease of the number of collisions, it prolongs significantly the lifetime of the network and delays the death of the first node while increasing both the throughput performance and the sending bit rate/throughput fairness among contending flows.